A mechanism for development of education management systems to increase the involvement of universities in production activities of the enterprise - E. V. Khodoreva; V. V. Shalay (Омский научный вестник: Серия "Общество. История. Современность", 2024)
The article examines mechanisms for deepening interaction between universities and enterprises in order to improve the quality of training of specialists and solve scientific and production problems, first of all, considering the problems of organizing production on the basis of a university, in particular, the problems of creating small innovative enterprises in a university environment and the possibility of commercialization are considered scientific and educational activities. The authors consider the features of the activities of small innovative enterprises and emerging risks. They offer mechanisms for building relationships with industrial partners. They pay attention to the rather complex procedure and rules for creating production activities on the basis of a university, analyze the experience of the functioning of small industrial enterprises in Russia, and highlight several problems that in one way or another hinder the widespread organization of production on the basis of universities. The scientific novelty of the article is the attempt to combine into a single system all forms and methods of interaction between the university, school and industrial partner through the creation of a holding company based on basic departments. The main research methods: studying the experience of the country’s leading universities, through the analysis of their charters and the analysis of Internet resources on the functioning of small innovative enterprises — in universities.